Understanding plant cell morphogenesis requires real-time monitoring of cell wall polymers. (February 2015) - Altartouri, Bara; Geitmann, Anja
Highlights: Dynamic arrangement of cell wall polymers regulates the growth pattern of plant cells. Valuable tools have recently been developed to visualize cell wall polymers in living cells. Small molecular probes and metabolic labeling open a new avenue to understanding the cell wall dynamics during cell expansion. Abstract : Plant cell development and growth are determined by the expansion pattern of the cell wall, a matrix of mixed polysaccharide polymers and proteins. To understand the different roles of these polymers in the regulation of the morphogenetic process, their spatial dynamics need to be monitored over time. Recent developments in the live cell labeling of polysaccharides include specific dyes whose insertion into the wall does not interfere with wall properties and growth, as well as metabolically inserted labeling. The present review explains the motivation and necessity for novel polysaccharide labeling techniques and provides an overview of the insight gained with these strategies.